BUSINESS FEASIBILITY ANALYSIS OF D’SWEETY LAYERS DESSERT CAKE - Putri, Berliana; Sonny, Sonny (FIRM Journal of Management Studies, 2023)
Dessert is a food served as a cover after the main food that is often found in various countries, including Indonesia. In Indonesia, dessert is usually called "makanan pencuci mulut". Dessert is identical with a sweet taste that is able to arouse the appetite of those who see it because of its attractive appearance. Therefore, an analysis will be carried out regarding the feasibility of the business in the dessert industry to be able to determine the sustainability of the business. In this business plan, a name will be given according to the dessert product that will be launched later, namely D'Sweety Layers which can describe a layered dessert cake with a sweet taste, which is called layers crepes cake. The target audience segmentation is the millennial generation and Z generation, who have so far been accustomed to following trends. Then expand the range not only offline stores but can be ordered online through the food delivery platform.